El oro o el agua, el caso del páramo de Santurbán (2017)
The article describes the situation of the Páramo de Santurbán after the intervention of the mining companies and shows its importance as a strategic ecosystem and a source of mineral wealth. Identifying the causes that make it attractive to the Páramo to strengthen mining activity there, as well as the consequent destruction of the ecosystem and the impact of its resources. Likewise, this study analyzes the social conflicts in the municipalities in Santurbán’s area of influence and highlights the confrontation between the country’s development model based on large-scale mining, the conservation of strategic ecosystems, communities that have opted for water rather than gold and people who have traditionally been miners, an activity that is their only livelihood and which now has an uncertain future due to the direction that the mining issue in Colombia is taking.